Impact of plant growth-promoting rhizobacteria on root colonization potential and life cycle of Rhizophagus irregularis following co-entrapment into alginate beads - Suarez Chacon, J. (2016)
Aims: This study aimed at evaluating the impact of seven plant growth-promoting rhizobacteria (PGPR) on root colonization and life cycle of Rhizophagus irregularis MUCL 41833 when co-entrapped in alginate beads. Methods and Results: Two in vitro experiments were conducted. The first consisted of the immobilization of R. irregularis and seven PGPR isolates into alginate beads to assess the effect of the bacteria on the pre-symbiotic growth of the fungus. In the second experiment, the best performing PGPR from experiment 1 was tested for its ability to promote the symbiotic development of the AMF in potato plantlets from three cultivars. Results showed that only one isolate identified as Pseudomonas plecoglossicida (R-67094) promoted germ tube elongation and hyphal branching of germinated spores during the pre-symbiotic phase of the fungus. This PGPR further promoted the symbiotic development of the AMF in potato plants. Conclusions: The co-entrapment of Ps. plecoglossicida R-67094 and R. irregularis MUCL 41833 in alginate beads improved root colonization by the AMF and its further life cycle under the experimental conditions. Significance and Impact of the Study: Co-entrapment of suitable AMF-PGPR combinations within alginate beads may represent an innovative technology that can be fine-tuned for the development of efficient consortia-based bioformulations. © 2016 The Society for Applied Microbiology.